2005
DOI: 10.1037/0894-4105.19.5.591
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Processes Supporting Causal Perception and Causal Inference in the Brain.

Abstract: An understanding of relations between causes and effects is essential for making sense of the dynamic physical world. It has been argued that this understanding of causality depends on both perceptual and inferential components. To investigate whether causal perception and causal inference rely on common or on distinct processes, the authors tested 2 callosotomy (split-brain) patients and a group of neurologically intact participants. The authors show that the direct perception of causality and the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 59 publications
4
71
0
Order By: Relevance
“…also found that when spatiotemporal contiguities were compared with conjoint spatial and temporal violations, activity in the right prefrontal cortex increased, suggesting that activity in the right prefrontal cortex is associated with causal integration as a whole. This suggestion is consistent with data of Roser et al (2005) who had split-brain patients perform causal judgments of billiards balls collisions. Causal and noncausal events were randomly presented to either their left or right visual fields, and patients' perceptions of spatiotemporal contiguities were more accurate on right visual-field trials than on left visual-field trials.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…also found that when spatiotemporal contiguities were compared with conjoint spatial and temporal violations, activity in the right prefrontal cortex increased, suggesting that activity in the right prefrontal cortex is associated with causal integration as a whole. This suggestion is consistent with data of Roser et al (2005) who had split-brain patients perform causal judgments of billiards balls collisions. Causal and noncausal events were randomly presented to either their left or right visual fields, and patients' perceptions of spatiotemporal contiguities were more accurate on right visual-field trials than on left visual-field trials.…”
Section: Introductionsupporting
confidence: 81%
“…A study with neurophysiological patients supports this claim. Using light switches and lightboxes, Roser et al (2005) found that split-brain patients judged temporal switch-on/light-on and switch-off/light-off contiguities as causal relations only when stimuli were presented in the left visual field. They concluded that the left hemisphere outperforms the right hemisphere at judging such abstract causal events.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding task performance, Hogarth (2001) and Plessner and Czenna (2008) would undoubtedly call on two independent knowledge systems (see also Fodor, 1985), one covering explicit understanding (including prediction) and the other addressing tacit understanding (including recognition). Data from split-brain adults (Roser, Fugelsang, Dunbar, Corballis, & Gazzaniga, 2005) suggest potential relevance for motion; hemispheric differences were detected over ''causal perception'' of motion (albeit horizontal, not vertical) and ''causal inference,'' equivalent to tacit and explicit processing, respectively. Yet although a ''separate systems approach'' cannot be rejected, it is rather implausible.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the intervention judgements undoubtedly require reflective reasoning. Judgements based on perceived causality are known to be affected by quite different types of task parameters than those based on more inferential processes (Schlottmann & Shanks, 1992), and it has recently been argued that they involve quite different brain structures (Roser, Fugelsang, Dunbar, Corballis, & Gazzaniga, 2005). It is possible that causal judgements that arise from more perceptually based processes might not easily support intervention judgements, and it may be the case that it is only with development that they do.…”
Section: Judgements About Interventionsmentioning
confidence: 96%